2018
DOI: 10.1155/2018/8092713
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Engineered Resveratrol‐Enriched Rice Inhibits Neuroinflammation in Lipopolysaccharide‐Activated BV2 Microglia Via Downregulating Mitogen‐Activated Protein Kinase‐Nuclear Factor Kappa B Signaling Pathway

Abstract: Resveratrol, a natural stilbenoid, is produced by several plants, especially grape vines. Its strong potency against obesity, metabolic disorders, vascular disease, inflammation, and various cancers has already been reported. Large amounts of wine or grapes need to be consumed to obtain the amount of resveratrol required for biological activity. Pure resveratrol at concentrations as low as 10 μM induces cytotoxicity to normal cells. To overcome these limitations, we prepared genetically modified resveratrol-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…AGEs and LPS can activate RAGE and toll like receptor 4 (TLR4) receptors, respectively, to exert their inflammatory effects through downstream signaling. The activation of RAGE and TLR4 in microglia or macrophage share common inflammatory pathways, indicating their role in neuroinflammation [ 27 , 34 , 44 , 45 , 46 ]. SFN showed a strong potency to inhibit microglial activation to the inflammatory phenotype and to increase the levels of anti-inflammatory phenotypic markers in LPS-activated microglia [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AGEs and LPS can activate RAGE and toll like receptor 4 (TLR4) receptors, respectively, to exert their inflammatory effects through downstream signaling. The activation of RAGE and TLR4 in microglia or macrophage share common inflammatory pathways, indicating their role in neuroinflammation [ 27 , 34 , 44 , 45 , 46 ]. SFN showed a strong potency to inhibit microglial activation to the inflammatory phenotype and to increase the levels of anti-inflammatory phenotypic markers in LPS-activated microglia [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…BV2 cells (4 × 10 4 cells per well) were seeded onto a 96-well plate and incubated overnight. Cells were treated with either vehicle (control) or different doses of SFN (dissolved in DMSO with a final concentration of 0.05%) 30 min prior to MGO-AGEs stimulation and incubated for an additional 24 h. Nitrite production was measured by Griess reagent assay, as described previously [ 27 ]. Conditioned medium from treated cells was mixed with an equal volume of Griess reagent in a new 96-well plate for the measurement of nitrite production, as described previously [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that the protective effect of resveratrol against neuropathic pain associated with VPN exhibits a dose‐dependent effect. Resveratrol has been reported to modulate NF‐κB‐mediated transcription of inflammatory proteins in lipopolysaccharide‐induced neuroinflammation via inhibition of NF‐κB translocation, IκB phosphorylation, and pro‐inflammatory cytokine production . Resveratrol has also been shown to inhibit pro‐inflammatory cytokines, including TNF‐α and IL‐1β, in the peripheral nerve system and relieves animals suffering from neuropathic pain .…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol has been reported to modulate NF-κB-mediated transcription of inflammatory proteins in lipopolysaccharide-induced neuroinflammation via inhibition of NF-κB translocation, IκB phosphorylation, and pro-inflammatory cytokine production. 41 Resveratrol has also been shown to inhibit pro-inflammatory cytokines, including TNF-α and IL-1β, in the peripheral nerve system and relieves animals suffering from neuropathic pain. 18,19 Data from the molecular study support the concept that resveratrol modulates NF-κB-medicated neuroinflammation in VPN induced by IR through inhibiting the IκB phosphorylation and NF-κB translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that resveratrol suppresses the inflammatory cytokines IL-1 β and TNF- α in hypoxia-induced cytotoxicity in BV2 microglial cells by inhibition of the MAPK and NF- κ B signaling pathways [ 127 ]. Similarly, resveratrol-enriched rice attenuates several inflammatory cytokines in LPS-activated BV2 microglial cells by suppression of MAPK signaling pathways and NF- κ B translocation [ 128 ]. There is a study on the neuron cells that found that resveratrol decreases the inflammatory cytokine TNF- α and neuron damage in the hippocampus of an alcohol-induced neurodegeneration rat through the p38 MAPK pathway [ 129 ].…”
Section: Sirt1 and Neuroinflammationmentioning
confidence: 99%